ANALISIS TEKNIKAL HARGA SAHAM PADA PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Susanti, Nuraidah Puput; Nurdin, Djayani; Kasim, Muh. Yunus (Katalogis, 2018)
This study aims to find out and analyze stock price movements and the application of ARIMA & ARCH / GARCH models in state-owned enterprises listed on Indonesia Stock Exchange. This research is a descriptive study with a quantitative approach. Data is collected through a list of stock prices for each company as many as 19 companies from January 2015 to December 2017 at www.idx.co.id. The data is analyzed by charting the stock price movements then describing the factors that influence the rise and fall of stock prices. After that, modelling is carried out based on data. The results show that the average stock price movements in 2015 decreased due to global economic conditions such as the weakening rupiah exchange rate against the US dollar, the decreasingÂ price of coal and nickel commodities, falling demand for imported raw materials from China, rising world oil prices, company policies in expansion, and government policies in the infrastructure sector. In 2016, the stock price movement rose again because the global economy is getting better and the average stock price movements tended to be stable in2017. The model used in stock price determination in companies such as PGAS, BBRI, and BMRI is the ARIMA model (1,0,1), which is sufficient to be used at the stock price when the normality requirements are met. While the stock prices of PTBA, ANTM, TINS, KRAS, SMBR, SMGR, INAF, KAEF, ADHI, WIKA, PTPP, GIAA, TLKM, JSMR, BBNI, and BBTN companies use GARCH models (1,0,1) which indicate volatility in the data that causes an error contains homoskedasticity and results in the failure to meet normal requirements on the model.